(3HjGf GdeUGOQI GdeTghQI ddMceGAs
(3ChdgG (B:s
(3Cbhd HYO MeO Gddg ejSQ cd YSjQ Cf GdJYdjeGJ HCSQgG hNUhUkG GdgfOSGJ eY hVhM eSGdcgG hhKGbI bhGYOgG dG JTHg SGFQ GdYdhe hGdUfGYGJ ai EQJHGW GdCLRGA s
(3BNQgG (B:s
(3Edi HjGf dehVY HjGfgeG ai Yde BNQ ZjQ GdgfOSI jchf Ydi SHjd GdeUGOQI aMSH agPG eG CQOJ Cf CYQVI Ydi GdBQGA GdTQjaI s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGfis
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI jhJG s
Keywords: (3GdQjGVjGJs